(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
This article examines the life and work of the famous French poet-fabulist of the 17th century Jean de la Fontaine. The diversity, rhythmic perfection of his works, skillful use of archaisms in them, a sober view of the world and their vivid imagery are analyzed.